EXTRACURRICULAR EDUCATIONAL ACTIVITY AS THE COMPOSITION OF SYSTEM OF FORMING THE SOCIAL AND LEGAL COMPETENCE OF FUTURE SOCIAL WORKERS - Oleg Lisovets (Vasyl Stefanyk Precarpathian National University, 2018)
The article the forms and methods of extracurricular educational activity of students-future social workers, contributing to the formation of their social and legal competence are analyzed. The extracurricular educational activity as planned academic, practical and research activities of students, performed in non-auditing time are defined. This happens in accordance with the tasks and instructions of the teacher, but without his direct participation. The forms and methods of independent work of students (preparation for seminars, practical tasks and individual tasks) in the study of educational disciplines of social and legal direction are considered.The social and legal content of the practice (study, volunteer, educational, industrial) of students of the specialty "Social work" is determined: studying normative documents, familiarization with the experience of protecting the rights of clients, development and implementation of measures, protection programs.The specifics of research activities of students of future social workers on the study of social and legal problems and cases are described. Among the forms of organization of this work we have identified: organization of student research (course, diploma, master's thesis, scientific reports, theses, articles); ensuring participation of students in scientific meetings (conferences, round tables, seminars); creation and support of student scientific communities (problem group, scientific circle).The experience of introducing extracurricular forms and methods of work within the framework of realization of the model of the system of formation of social and legal competence of future social workers is presented. Key words: extracurricular educational activity, social and legal competence, independent work, research work.